2021
DOI: 10.1073/pnas.2014681118
|View full text |Cite
|
Sign up to set email alerts
|

Butyrate enhances CPT1A activity to promote fatty acid oxidation and iTreg differentiation

Abstract: Inducible regulatory T (iTreg) cells play a crucial role in immune suppression and are important for the maintenance of immune homeostasis. Mounting evidence has demonstrated connections between iTreg differentiation and metabolic reprogramming, especially rewiring in fatty acid oxidation (FAO). Previous work showed that butyrate, a specific type of short-chain fatty acid (SCFA) readily produced from fiber-rich diets through microbial fermentation, was critical for the maintenance of intestinal homeostasis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 51 publications
0
54
0
2
Order By: Relevance
“… Raud et al, 2018 found that naive CD4 + T cells isolated from mice with CPT1 deletion in T cells (TCPT1 mice) did not seem to have any defect in iTreg differentiation and proposed that the phenotypes induced by high-dose CPT1 inhibitor, etomoxir (>100 μM), were due to the off-target effect. However, we found that siRNA-mediated Cpt1 knockdown or low-dose etomoxir (5 μM), which inhibits CPT1 without introducing off-target effects, impaired iTreg differentiation in vitro ( Hao et al, 2021 ; O'Connor et al, 2018 ; Figure 2F , Figure 2—figure supplement 5B ). Of note, TCPT1 mice reported in Raud et al, 2018 survived from the lack of CPT1.…”
Section: Discussionmentioning
confidence: 89%
“… Raud et al, 2018 found that naive CD4 + T cells isolated from mice with CPT1 deletion in T cells (TCPT1 mice) did not seem to have any defect in iTreg differentiation and proposed that the phenotypes induced by high-dose CPT1 inhibitor, etomoxir (>100 μM), were due to the off-target effect. However, we found that siRNA-mediated Cpt1 knockdown or low-dose etomoxir (5 μM), which inhibits CPT1 without introducing off-target effects, impaired iTreg differentiation in vitro ( Hao et al, 2021 ; O'Connor et al, 2018 ; Figure 2F , Figure 2—figure supplement 5B ). Of note, TCPT1 mice reported in Raud et al, 2018 survived from the lack of CPT1.…”
Section: Discussionmentioning
confidence: 89%
“…Butyrate and propionate facilitate the extrathymic differentiation of Treg cells by promoting the acetylation of Foxp3 promotor locus and FOXP3 protein, to enhance FOXP3 transcription and protein stability, as well as its TF function [77]. Apart from acting as an HDAC inhibitor, butyrate can be transformed into butyryl-CoA with the help of acyl-CoA synthetase shortchain family member 2 (ACSS2), to antagonize the inhibitory effect of malonyl-CoA on CPT, thus by upregulating CPT1A activity promotes FAO, and facilitates iTreg differentiation [104] (Fig. 2c).…”
Section: Scfas and Cd4 + T Lymphocyte Subtype Prevalencementioning
confidence: 99%
“…For example, vitamin B9, the synthesis of which depend on Bifidobacterium and Lactobacillus, is a survival factor for Treg cells ( Kunisawa et al., 2012 ) ( Figure 5 , III ). Butyrate derived from gut microbiota is conducive to shaping the intestinal immune homeostasis by inducing the differentiation of colonic inducible Treg cells ( Furusawa et al., 2013 ) through enhancing fatty acid oxidation dependent on carnitine palmitoyl transferase 1A (CPT1A) ( Hao et al., 2021 ). Butyrate also promotes the generation of Treg cells by upregulating gene expression of histone acetylation ( Arpaia et al., 2015 ) ( Figure 5 , IV ).…”
Section: Gut Microbiota Is Involved In the Development Of Oa Through ...mentioning
confidence: 99%
“…III Vitamin B9 contributed to the survival of Treg cells ( Kunisawa et al., 2012 ). IV Butyrate modulated the generation and differentiation of Treg cells by up regulating histone acetylation ( Arpaia et al., 2015 ) and enhancing fatty acid oxidation dependent on carnitine palmitoyl transferase 1A (CPT1A) ( Hao et al., 2021 ). IFN, interferon.…”
Section: Gut Microbiota Is Involved In the Development Of Oa Through ...mentioning
confidence: 99%